Cellular distribution studies of the nitric oxide‐generating antineoplastic prodrug O2‐(2, 4‐dinitrophenyl)1‐((4‐ethoxycarbonyl)piperazin‐1‐yl)diazen‐1‐ium‐1, 2‐diolate formulated in Pluronic P123 micelles. (10th July 2013) - Kaur, Imit; Terrazas, Moises; Kosak, Ken M.; Kern, Steven E.; Boucher, Kenneth M.; Shami, Paul J.
Abstract Objective Nitric oxide (NO) possesses antitumour activity. It induces differentiation and apoptosis in acute myeloid leukaemia (AML) cells. The NO prodrug O2‐(2, 4‐dinitrophenyl)1‐((4‐ethoxycarbonyl)piperazin‐1‐yl)diazen‐1‐ium‐1, 2‐diolate, or JS‐K, has potent antileukaemic activity. JS‐K is also active in vitro and in vivo against multiple myeloma, prostate cancer, non‐small‐cell lung cancer, glioma and liver cancer. Using the Pluronic P123 polymer, we have developed a micelle formulation for JS‐K to increase its solubility and stability. The goal of the current study was to investigate the cellular distribution of JS‐K in AML cells. Methods We investigated the intracellular distribution of JS‐K (free drug) and JS‐K formulated in P123 micelles (P123/JS‐K) using HL‐60 AML cells. We also studied the S‐glutathionylating effects of JS‐K on proteins in the cytoplasmic and nuclear cellular fractions. Key findings Both free JS‐K and P123/JS‐K accumulate primarily in the nucleus. Both free JS‐K and P123/JS‐K induced S‐glutathionylation of nuclear proteins, although the effect produced was more pronounced with P123/JS‐K. Minimal S‐glutathionylation of cytoplasmic proteins was observed. Conclusions We conclude that a micelle formulation of JS‐K increases its accumulation in the nucleus. Post‐translational protein modification through S‐glutathionylation may contribute to JS‐K's antileukaemic properties.